Partnership and corporation accounting and their legal bases - Macapilit, Cecilia Hugo- (Manila, Philippines : Rex Book Store, 2010)
This book is prepared to complete the basic Accounting concepts on business organizations. The first Accounting book deals with single or sole proprietorship alone. But this textbook deals with a more complicated form of business organizations, partnerships and corporations. The students will be equipped with the different features of partnerships and corporation. Partnerships and corporations are legal entities and the students should know the legal provisions behind them. Myriad problems are encountered by these kind of business organizations and therefore, they should be able to to support them.
Review of the Accounting Cycle 1 -- Partnership 21 -- Partnership Accounting 29 -- Partnership: Division of Profits 53 -- Partnership Dissolution 87 -- Partnership Dissolution: Liquidation 110 -- Corporation: Formation and General Provision 127 -- Accounting for Corporations 145 -- Stockholder's Equity 179 -- The Voucher System 202 -- References 215 -- Index 216.
Keywords: BANKS AND BANKING -- PHILIPPINES